High-Level Design and Implementation of a Configurable Cryptosystem With a Novel Chaos-Enhanced Function - Medien Zeghid; Hassan Yousif Ahmed; Akhtar Nawaz Khan (IEEE Access)
The widespread availability of networks has significantly increased the exposure of data to security threats, necessitating robust encryption methods. While existing symmetric block ciphers offer varying levels of security, they are susceptible to advancements in cryptanalysis. From this perspective, in this article, we present an efficient approach to enhancing the security of these ciphers through the integration of chaos theory. The key to this enhancement is a newly developed adaptive chaotic map based on sine map and the dynamic interplay of two key parameters (rn,k $_{n}$ ). Of course, the efficiency of the proposed chaotic map is demonstrated by the time evolution, the Bifurcation diagram, Permutation Entropy (PE), Fuzzy Correlation Dimension (FCD), and Lyapunov Exponent (LE) analyses and comparison with the existing reported maps. Thereafter, by applying chaos theory to address the limitations of default cipher parameters, and operating modes and to control S-boxes, permutation functions, key schedules, data masking, we introduce nonlinearity and diffusion, making the block ciphers more resistant to attacks. Through extensive simulations and evaluations, we demonstrate the effectiveness of our approach in strengthening the security of the enhanced ciphers against pattern, statistical, differential, key sensitivity, Linear, and Padding Oracle attacks. Additionally, we present a high-level design and implementation of a configurable cryptosystem using SystemC. The configurable design allows for flexibility in integrating different ciphers and adapting to evolving security needs.